Root growth in tomato seedlings in response to bacterial inoculation Serratia sp. (Research, Society and Development, 2020)
Growth-promoting rhizobacteria are soil bacteria that inhabit the surrounding root, and are directly or indirectly involved in promoting plant growth and development. The productivity efficiency of these groups of microorganisms can be applied to planting crops, providing an interesting alternative for minimize the negative effects of water deficit. The objective of this study was to verify if the mechanism of growth promotion of the bacterium is similar to that promoted by polyethylene glycol (PEG) and to compare the possible effects of water stress on the tomato against the effects of inoculation of the bacterium Serratia sp. The methodology was based on in vitro bioassays using tomato (Solanum lycopersicum L.) seedlings, kept in a growth chamber with temperature of 25 °C and photoperiod of 12 hours. The results revealed that the promotion of tomato root growth by Serratia sp. is similar to that promoted by PEG 7%, differing significantly from the results found with different doses of indoleacetic acid (IAA). The promotion of root growth in tomatoes by Serratia sp. and PEG 7% partly indicates a physical effect, since the water restriction imposed by the PEG molecule decreases the water movement capacity, also observed by bacteria, when colonizing plant tissues and cells (biofilm) reducing the hydraulic conductivity of water through the root. Stimulation to promote root growth in tomatoes cannot be reproduced by auxin.